Estrategia psicoeducativa para el desarrollo del aprendizaje en niños con trastorno por déficit de atención e hiperactividad (2024)
In this research the general objective is to identify psychoeducational strategies for the development of learning in children with attention deficit and hyperactivity disorder in the Educational Institution N°10 José Domingo Boscán del Municipio Maicao, the applied methodology was under the qualitative approach, the Type and Design corresponds to the Participatory Research- 11 Action (IAP), the Instruments applied was the interview, through a script and observation, the sample was made up ofA semi-structured interview with open-ended questions structured according to the categories: Psychoeducational Strategies and Attention Deficit and Hyperactivity Disorder and subcategories was applied for the information collection: Differentiated Levels and Psychological Elements. For the process of analysis of the results, the Analysis Units are considered It is concluded that caring for children with ADHD from individual differentiated levels, family and group, facilitates the teacher to obtain accurate information of the condition present in the student and thus apply psychoeducational strategies in accordance with the need present in the child’s action to promote the development of learning and the possibility of develop their potential to discover their strengths to face everyday life in a more adaptive way.